The Guatemalan National Revolutionary unit: the long collapse. Issue 6 (18th September 2016) - Allison, Michael E.
ABSTRACT: The Guatemalan National Revolutionary Unit (URNG) fought one of the longest and bloodiest civil wars in recent Latin American history. In 1996, the URNG and the Government of Guatemala signed a Firm and Lasting Agreement ending the country's civil war and initiating the URNG's post-war life as a political party. After finishing third in its initial electoral competition, the URNG has since been unable to capture more than 4% of the vote, on its own or in coalition, leaving it a minor political party. What explains the poor electoral performance of the URNG as a political party? Based upon fieldwork, elite interviews, and analysis of electoral data, I argue that the URNG's minor party performance was caused by both organizational and institutional factors.